Assessment of Technological Gap and Performance of CombinedManagement Approach for Pod Borer in Chickpea (Indian Journal of Extension Education, 2011)
Chickpea [Cicer arietinum Linn.] is one of the important and oldest pulse crop cultivated in India and occupying 7.10 million hectares area and contributing 5.75 million tones yield to the national pulse basket. It is grown through out the country excepting on high altitude of northern and north eastern regions and coastal peninsula. The major chickpea producing states are Andhra Pradesh, Madhya Pradesh, Rajsthan, Uttar Pradesh, Maharastra, Haryana, Karnataka, Gujrat, Bihar and West Bengal. The area production and productivity of chickpea in the states of Uttar Pradesh 6764884 hectares, 500799 metric tonnes and 7.42q/ha.,respectively. Some districts of Uttar Pradesh i.e. Banda and Hamirpur have more than one lakh hectare area under chickpea. Highest productivity has been reported from Azamagarh and Mau(1269 kg/ha). The area, production and productivity of chickpea in the district Balrampur of Uttar Pradesh are 490 hectares, 366 metric tonnes and 7.48 q/ha, respectively.